2018
DOI: 10.1101/327049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplemental vibrotactile feedback of real-time limb position enhances precision of goal-directed reaching

Abstract: We examined vibrotactile stimulation as a form of supplemental limb state feedback to enhance on-going control goal-directed movements. Subjects wore a two-dimensional vibrotactile display on their non-dominant arm while performing horizontal planar reaching movements with their dominant arm. The vibrotactile display provided feedback of hand position such that small hand displacements were more easily discriminable using vibrotactile feedback than with intrinsic proprioceptive feedback. When subjects relied s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 46 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…Vibrotactile feedback (VTF) is an inexpensive and non-invasive way of conveying supplemental information to a user without taxing visual or auditory attention. Common forms of vibrotactile cues include continuous state feedback (Risi et al 2019; Krueger et al 2017; Ferris and Sarter 2011), continuous error feedback relative to some goal (Cuppone et al 2016; Wall et al 2001; Tzorakoleftherakis et al 2016), and indicators of undesirable conditions [i.e., alarms; (Ferris and Sarter 2011)]. In each of these cases, the vibrotactile cues should be designed so that the encoded information is clearly perceptible.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrotactile feedback (VTF) is an inexpensive and non-invasive way of conveying supplemental information to a user without taxing visual or auditory attention. Common forms of vibrotactile cues include continuous state feedback (Risi et al 2019; Krueger et al 2017; Ferris and Sarter 2011), continuous error feedback relative to some goal (Cuppone et al 2016; Wall et al 2001; Tzorakoleftherakis et al 2016), and indicators of undesirable conditions [i.e., alarms; (Ferris and Sarter 2011)]. In each of these cases, the vibrotactile cues should be designed so that the encoded information is clearly perceptible.…”
Section: Introductionmentioning
confidence: 99%
“…Risi et al also showed that over the course of two days of VTF-guided reach training, target capture accuracy further improved toward the limits of vibrotactile perception, even though that level of accuracy exceeded the level attainable using proprioceptive control alone [14]. Successful use of VTF requires the user to sense vibration, decode the information it contains, and produce a task-appropriate response [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…Successful use of VTF requires the user to sense vibration, decode the information it contains, and produce a task-appropriate response [15, 16]. Given that VTF-guided reaching in Risi et al took approximately 2.5 times longer to perform than movements without VTF [14], it is likely that the use of online VTF to plan and control movements imposes additional cognitive loads sufficient to degrade movement timing. Thus, using real-time VTF to assist in performing simultaneous tasks, such as reaching for a glass of water while reading or talking, may be difficult until the use of VTF becomes automatic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most research has focused on the recovery of impaired motor function [78,[97][98][99], and the somatosensory function received less attention [84]. Previous studies used vibrotactile information to augment healthy and impaired somatosensation either by communicating error or state information via vibration [100][101][102]. In addition, skin brush information was used to convey directional information as part of efforts to substitute proprioception [84].…”
Section: Haptics For Rehabilitationmentioning
confidence: 99%